Clonagem e caracterização molecular de cisteíno proteases de Carica candamarcensis - Caroline Furtado Junqueira (2007)
Caricaceaes are important source of proteolytic enzymes belonging to the group of cysteine proteinases. These enzymesare economically relevant to several industrial and therapeutic applications. Cysteine proteinases from Carica candamarcensis are being studied by our group for their high proteolytic activity stimated between five to eight fold higher than enzymes from C. papaya. Although four of these enzymes were previously characterized at the proteolytic level, however, none of them were cloned from a mRNA. Using an mRNA plant leaf preparation, cDNA molecules were synthesized by RT-PCR and cloned into sequence and expression vectors. Here are related the results of a cloning and molecular characterization regarding to two cysteine proteinases from this species.